ERKIN AZAM'S SKILLS OF EXPRESSING PERSONAL SPIRIT (BASED ON THE FILMSTORY "ZABARJAD") (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article reveals Erkin Azam's skill in creating character and depicting moods with examples based on the filmstory "Zabarjad". The system of images in the work is analyzed. The author's personal conclusions are based on the opinions of well-known scientists and young researchers.